Models For Entering International Markets - zohreh dehdashti shahrokh (مطالعات مدیریت بهبود و تحول, 2007)
Internationalization Process means export development. Firms are located differently on the export development process continuum and in each stage need different services for export development.Internationalization process have attracted attention of many researches. In this article four main models will be reviewed such as : Uppsala Schools Models (U-Models), Innovation - Based Models ( I• Models), Network Models and Resource- Based Models.